PENGARUH PRODUK, HARGA DAN LAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN SEPEDA MOTOR HONDA (Studi Kasus Pada PNS di Kabupaten Kepulauan Meranti) - Setyawan, Winardi; Alwie, Alvi Furwanti; Musfar, T. Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to know the Influence of Product, Price and After Sales Service to Purchase Decision and Satisfaction of Honda Motorcycle Consumer (Case Study On Civil Servant In District of Meranti Island). The object in this study is a Honda motorcycle. This study uses Consumer Satisfaction as endogenous variable and Purchase Decision as intervening variable. While the exogenous variables in this study are Product, Price and After Sales Service. The population in this study is all civil servants in the district of Meranti Islands who have bought Honda motorcycles as many as 3,532 people and the sample used in this study 100 people. This research uses simple random sampling with criteria that decide the purchase of Honda motorcycle. Data taken from the respondents using the core questionnaire. The method of analysis used in this research is path analysis using SPSS (Statistical Package for Social Science) version 21. The results of this study indicate that the product has a positive and significant effect on Purchase Decision. Price has a positive and significant effect on Purchase Decision. After sales service has a positive and significant impact on Purchase Decision. Products have a positive and significant impact on Consumer Satisfaction through Purchase Decision. Price has a positive and significant effect on Consumer Satisfaction through Purchasing Decision. After Sales Service has a positive and significant impact on Consumer Satisfaction through Purchase Decision. Purchase Decision has positive and significant impact on Consumer Satisfaction.Keywords : Product, Price, After Sales Service, Purchase Decision, Consumer Satisfaction.